State of the ART: practical evaluation and management of pleural infection - Yvette A. Yeboah-Kordieh; Diana Mihalache; Udit Chaddha (Current Opinion in Pulmonary Medicine, 2026)
Purpose of review This review synthesizes recent evidence and provides a stepwise approach to management, emphasizing timely recognition of treatment failure, appropriate escalation of therapy, and individualized decision-making to optimize clinical outcomes. Recent findings The cornerstone of pleural infection management is appropriate antibiotic therapy and effective pleural drainage. Most infections are polymicrobial, with anaerobic organisms predominating. Image-guided chest tube drainage remains the standard initial intervention. Early recognition of inadequate drainage or persistent pleural infection-related sepsis through close clinical, biochemical, and radiographic assessment is essential to facilitate timely escalation of care. Intrapleural enzyme therapy (IET) reduces the need for surgery, and emerging evidence suggests that lower-dose tissue plasminogen activator (tPA) regimens may preserve efficacy. Current evidence supports a sequential management strategy in which IET precedes surgery, with early thoracic surgical consultation and prompt recognition of IET failure to avoid delays that may increase surgical morbidity. Summary Successful management of pleural infection depends on early source control, vigilant assessment of treatment response, and timely escalation of care. A structured, stepwise approach that integrates antibiotics and effective pleural drainage, early use of IET when indicated, and prompt surgical consultation for nonresponders offers the best opportunity to improve outcomes while minimizing morbidity.